Analisa Keputusan Penerapan Preventive Maintenance Pada Boyd Crusher di Perusahaan Penunjang Industri Pertambangan - Girman Sihombing; Evy Priyanti; Bayu Nur Kuncoro; Sofyan Wahyu (LPPM Universitas Bina Sarana Informatika, 2022)
Mining industry has the closed relation which is not separated from some types of company. Those service company are very important for mining activities. The support company is a company who give service for making the mining activities run well. Research or analysis service for solid or water mineral content is one of the support companies as state above. The purpose of this research is to know the often damage of spare parts of Boyd Crusher as one of main equipment of service company above. In this case, the coefficient value of the form and the time parameter must be known by using Weibull distribution, so that the maintenance method can be decided by applicating preventive maintenance concept. This research is done by using quantitative – qualitative method which based data around 1 year and the result is found that the Cylindrical Roller Bearing is the highest damage component. This finding is continued to be analysed by using fish bone diagram to know the main factor of those damages and the result is the less of routine lubrication and Lubricant excessive quantity for that component part where this part is made from metal material that has high friction.